Anti-IgE Treatment for Disorders Other Than Asthma - Stokes, Jeffrey (Frontiers in Medicine, 2017)
Immunoglobulin E (IgE) plays key roles in the pathogenesis of allergic diseases. For this reason, IgE-mediated immunologic pathways are an attractive target for therapeutic agents in allergic diseases. Omalizumab is a recombinant humanized monoclonal antibody that binds IgE and has been been used for the treatment of allergic asthma for over a decade. Currently omalizumab is approved for the treatment of allergic asthma and chronic spontaneous urticaria. Since IgE plays a critical role in other allergic diseases, anti-IgE therapy has been evaluated in other allergic diseases in small clinical trials and case reports. Omalizumab has demonstrated efficacy in treating allergic rhinitis, atopic dermatitis, physical urticarias, mast cell disorders, food allergy and other allergic diseases. In addition, the use of omalizumab with conventional allergen immunotherapy improves both safety and effectiveness.